Interaction of antitumoral fluorescent heteroaromatic compounds, a benzothienopyrrole and two thienoindoles, with DNA and lipid membranes - Abreu, Ana S. (2012)
Three tricyclic compounds, a benzothieno[2,3-b]pyrrole 1, a thieno[3,2-f]indole 2 and a thieno[2,3-e]indole 3, early synthesized by us, were evaluated for their capacity to inhibit the in vitro growth of three human tumor cell lines, MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and SF-268 (CNS cancer) and it was found that compound 1 is the most potent presenting the lowest GI50 values (7.9-14.1 µM). The photophysical properties of the three compounds (absorption and fluorescence) were studied in different solvents and in lipid membranes of dipalmitoyl phosphatidylcholine (DPPC), dioctadecyldimethylammonium bromide (DODAB), phosphatidylcholine from egg yolk (egg lecithin, Egg-PC) and dipalmitoyl phosphatidylglycerol (DPPG), considering future drug delivery applications using liposomes. Fluorescence measurements indicate that all the compounds incorporated in lipid membranes are mainly located in the lipid bilayer. Compounds 1 and 3 clearly detect the gel to liquid-crystalline phase transition, while compound 2 feels a more hydrated environment in DPPG and DODAB vesicles. Due to the antitumoral properties of the three fluorescent compounds, interactions with salmon sperm DNA were investigated using fluorescence techniques which allowed the determination of binding constants (Ki) and binding site sizes (n) for each compound. When compared with the thienoindoles 2 and 3, the benzothienopyrrole 1 showed the highest affinity to DNA. Quenching experiments with iodide ion showed that intercalation is the preferred mode of binding of the three compounds to the DNA molecule.